OPTIMIZATION OF THE CROSSFLOW MICROFILTRATION OF ARAZÁ JUICE (Eugenia stipitata) UNDER DIFFERENT OPERATION MODES - RAMÍREZ L., Ángelo G.; de los RÍOS C., Diego F.; VÉLEZ P., Carlos A.; GALLEGO O., Heidy L. (Vitae, 2011)
This study analyzed the effects of temperature and transmembrane pressure on the crossflow microfiltration process of arazá (Eugenia stipitata) juice treated with a commercial pectic enzyme preparation, thus finding the appropriate operation values of the process. Clarified arazá juice was obtained with a crossflow microfiltration pilot plant equipped with ceramic membranes with a 0.48 m2 total effective filtration area and mean pore diameter of 0.2 µm. The juice was evaluated at transmembrane pressures 1.5, 3.0 and 4.5 bar, and at temperatures of 30, 35 and 40ºC at different volumetric reduction factors. The tests were carried out using three systems (total recirculation, concentration, and continuous mode). In total recirculation, it was found that the most influential variable was the transmembrane pressures, and that the partial enzymatic liquefaction of the arazá juice, prior to microfiltration, produced an unusual pattern of permeate flux, characterized by an increase following an abrupt decrease at 4.5 bar and 6.5 m/s. In this case, the highest values of the flux were obtained when compared with those obtained during the crossflow microfiltration in concentration mode. After reaching the value of volumetric reduction factor (3.2), during the crossflow microfiltration in continuous mode, it was not necessary to stop the process as the volumetric reduction factor remained constant for the continuous removal of retained, achieving a high permeate flux in a short period of time 319 L/(h·m2), thus adding to the economic viability of the process.